Understanding the impact of digital technology on the well-being of older immigrants and refugees: A scoping review - Prince Chiagozie Ekoh; Tochukwu Jonathan Okolie; Fidel Bethel Nnadi; Oluwagbemiga Oyinlola; Christine A Walsh (Digital Health, 2023)
Background The fast-paced development of digital technologies in the areas of social media, pet robots, smart homes, and artificial intelligence, among others, profoundly influence the daily lives of older adults. Digital technology can improve the well-being and quality of life of older adults, older immigrants and refugees who suffer migration-associated stress, loneliness, health and psychosocial challenges. Aims The aim of this scoping review is to map out extant empirical literature that has examined the implication of digital technology among older refugees and immigrants. Methods Using a 1 five-stage framework, we conducted a scoping review of peer-reviewed empirical studies published in English with no time restrictions. We searched nine databases for the reviews, and abstracts were reviewed using Rayyan QCRi (c) before the full-text review. The comprehensive database search yielded 4134 articles, of which 15 met the inclusion criteria. Results The results of the review suggest that digital technology is essential to the well-being, quality of life of older immigrants and refugees, especially for maintaining and building new social support networks, navigating opportunities, coping with migration-induced stress through e-leisure, and staying connected to their culture. The literature also revealed poor utilisation of digital technologies amongst older immigrants and refugees, suggesting barriers to access. Conclusion The study concluded by highlighting the need for more research and interventions that focus on multiple strategies, including education for increased access to and utilisation of digital technology to ensure that more older migrants can benefit from the advantages of digital technology in a safe way.